Issue Cover. (12th August 2020) - Wei, Jingwei; Jiang, Hanyu; Gu, Dongsheng; Niu, Meng; Fu, Fangfang; Han, Yuqi; Song, Bin; Tian, Jie
Abstract : The cover image is based on the Review Article Radiomics in Liver Diseases: Current Progress and Future Opportunities by Jie Tian, Hanyu Jiang, Jing Wei Wei et al., https://doi.org/10.1111/liv.14555 .